Understanding the CO capture reaction through electronic structure analysis of four-membered-ring group-13/N- and B/group-15-based Lewis acid-base pairs - Zhang, Zheng-Feng; Su, Ming-Der (RSC advances, 2024)
Incomplete combustion yields a significant byproduct, known for its high toxicity to humans: gas phase carbon monoxide (CO). This study utilized several advanced theoretical methods to examine the factors contributing to the activation energy involved in CO capture by a frustrated Lewis pair (FLP) and to forecast the potential success of the CO capture reaction. The current theoretical findings indicate that among the four-membered-ring Group-13/N-FLP and B/Group-15-FLP molecules, only the B/N-based FLP-type molecule effectively captures CO, considering both thermodynamics and kinetics. According to the results obtained through energy decomposition analysis-natural orbitals for chemical valence (EDA-NOCV), it can be concluded that the donor-acceptor (singlet-singlet) model, rather than the electron-sharing (triplet-triplet) model, effectively characterizes the electronic structures in the CO trapping reaction involving four-membered-ring G13/G15-FLPs. Theoretical findings, derived from EDA-NOCV and frontier molecular orbital theory, demonstrate that the CO capture reaction by G13/G15-FLP involves two distinct bonding interactions. The first interaction is characterized by FLP-to-CO forward bonding, with the lone pair of G15 (G13/G15-FLP) donating to the empty p-π* orbital of carbon (CO), which predominates. The second interaction involves CO-to-FLP backward bonding, where the empty σ* orbital of G13 (G13/G15-FLP) accepts the lone pair of carbon (CO), albeit to a lesser extent. In summary, our theoretical findings indicate that the G13-C and G15-C bonds in the G15/G15-TS species with a four-membered ring can be classified as two dative single bonds. The importance of the interaction between Lewis bases and CO surpasses that of the interaction between Lewis acids and CO. Theoretical evidences in this study demonstrate a linear connection between the G13-G15 bond length within the four-membered-ring G13/G15-FLP and the activation barrier linked to CO capture. The activation strain model analysis in this study suggests that the activation energy required for bond formation primarily depends on the geometric deformation energy of G13/G15-FLP in capturing CO. Our DFT investigation shows that Hammond's postulate is obeyed by the CO catching reaction of the four-membered-ring G13/N-FLP, meaning that an earlier transition state is associated with a lower activation barrier, but not with the CO catching reaction of the four-membered-ring B/G15-FLP. The theoretical evidences reveal that in the four-membered-ring Group-13/N-based and B/Group-15-based Frustrated Lewis Pair (FLP)-assisted molecules, only the B/N-based FLP can undergo the CO catching reaction both kinetically and thermodynamically.